Studies of the Escherichia coli Rsd-sigma70 complex. - Westblade, L; Ilag, L; Powell, A; Kolb, A; Robinson, C; Busby, S (2004)
Escherichia coli Rsd protein was previously identified on the basis of its binding to the RNA polymerase sigma(70) subunit. The Rsd-sigma(70) complex has been studied using different methods. Our data show that Rsd associates with sigma(70) to form a complex with a stoichiometry of 1:1. Alanine scanning and deletion mutagenesis were used to locate regions of sigma(70) that are required for the formation of the Rsd-sigma(70) complex.